Obtenção de nanocelulose a partir de fibras de sisal e sua aplicação em fluidos de perfuração - Pessoa, Maria Eduarda Araújo (2022)
The growing interest in the properties of nanoparticles for application in drilling fluids is due to their high surface area, which improves rheological parameters and static filtration. Linked to this is the motivation to use resources from sustainable sources such as sisal, which are abundant and easy to grow in the northeastern region of Brazil and add value through the extraction of nanoparticles (NPs). Therefore, the present work aims at the formulation of water-based drilling fluids and the synthesis of a filtrate control additive, nanocellulose, derived from sisal to improve the rheological properties of clayey fluids. Nanocellulose was obtained by acid hydrolysis (56% sulfuric acid) where the fibers were pretreated with mercerization (NaOH, 4%) and bleach (NaClO2, 1.7%) and then with the addition of potassium acetate (0.5%, 0.5% ) and ethanol were centrifuged, and dried in an oven (60°C/18 h) to obtain the final dry particles. The dry material obtained was characterized by XRD, SEM, FTIR and TG/DTG, which could demonstrate the removal of a large part of the non-cellulosic material, obtaining samples of homogeneous size and smaller compared to the original material. Drilling muds were tested, namely: F1 to F7, muds with emulsified systems, F8 and F9, using xanthan gum and calcite, and clay muds, F10 to F13, with Closite 20A and F14 to F17, with sodium bentonite. Different proportions of dry nanocellulose (0.5%, 1.0% and 1.5% w/v) were tested in clayey liquids with specific rheology and static filtration properties. All formulated fluids showed experimental data better fitting the Herschel-Bulkley model, with an increase in stress and a consequent decrease in viscosity as the shear rate increased, and with thixotropic properties. Analyzing the behavior of nanocellulose addition in clay containing fluids, it was observed that the nanoparticle has an impact on the properties analyzed, but not enough to promote rheological and filtration changes with increasing concentration of this additive, even at low thicknesses of filter cake and low permeability.